2016
DOI: 10.1007/s11259-015-9650-5
|View full text |Cite
|
Sign up to set email alerts
|

FGF-21: promising biomarker for detecting ketosis in dairy cows

Abstract: The objective of this study was to investigate the measurement of serum fibroblast growth factor-21 (FGF-21), a protein mainly synthesized by the liver, as a sensitive biomarker for diagnosis of ketosis in dairy cows. Ninety Holstein-Friesian dairy cows (60 healthy and 30 ketosis cases) were selected and divided into a Ketosis group (K), and a Control group (C). We measured serum FGF-21 and other biochemical parameters by commercial ELISA kits. In a combined population of all 90 cows, we found that serum FGF-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Furthermore, the changes of many hormones involved in ketotic progression, such as fibroblast growth factor-21 (FGF-21) and bST (Schlegel et al, 2013;Gohary et al, 2014). Xu et al (2016) reported that the blood concentration of FGF-21 was significantly decreased in the ketotic cows. Du et al (2018) also reported that uncoupling of the bST axis might be a cause of ketosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the changes of many hormones involved in ketotic progression, such as fibroblast growth factor-21 (FGF-21) and bST (Schlegel et al, 2013;Gohary et al, 2014). Xu et al (2016) reported that the blood concentration of FGF-21 was significantly decreased in the ketotic cows. Du et al (2018) also reported that uncoupling of the bST axis might be a cause of ketosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, urine concentrations of 11 proteins including amyloid precursor protein, apolipoprotein (Apo) C-III, cystatin C, fibrinogen, hepcidin, human neutrophil peptides, osteopontin, VGF (non-acronymic) protein, serum amyloid A (SAA), the C1 inhibitor (C1INH), and transthyretin were decreased in ketotic cows [55]. The same authors reported that serum fibroblast growth factor-21 might be a promising biomarker for detecting ketotic cows [56]. It should be noted that these novel biomarkers have yet to be validated.…”
Section: Some Newly Identified Diagnostic Biomarkersmentioning
confidence: 99%
“…Meanwhile, a link between clinical ketosis in dairy cows and decreased milk production, rumen stagnation, constipation, decreased feed intake, as well as loss of body condition, and an association between hyperketosis and increased levels of oxidative stress has also been revealed [3]. Ketogenic cows have a lower milk yield, lower milk fat content, and higher concentrations of BHBA, NEFAs, interleukin (IL)-6, tumor necrosis factor (TNF), and lactic acid in serum compared with healthy cows [4,5,6], and the antioxidant capacity of ketone-causing bovine bodies is also greatly reduced [7]. High levels of NEFAs and BHBA are also associated with inflammatory responses during diseases such as cow mastitis and metritis.…”
Section: Introductionmentioning
confidence: 99%